2023
DOI: 10.1038/s41380-023-02188-8
|View full text |Cite
|
Sign up to set email alerts
|

Individual regional associations between Aβ-, tau- and neurodegeneration (ATN) with microglial activation in patients with primary and secondary tauopathies

Abstract: Abstractβ-amyloid (Aβ) and tau aggregation as well as neuronal injury and atrophy (ATN) are the major hallmarks of Alzheimer’s disease (AD), and biomarkers for these hallmarks have been linked to neuroinflammation. However, the detailed regional associations of these biomarkers with microglial activation in individual patients remain to be elucidated. We investigated a cohort of 55 patients with AD and primary tauopathies and 10 healthy controls that underwent TSPO-, Aβ-, tau-, and perfusion-surrogate-PET, as … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 87 publications
0
9
0
Order By: Relevance
“…These findings are in line with in vivo observations that point to associations between microglial activation and tau pathology, and with recent large GWAS studies underscoring the interaction between microglial, Aβ and tau-linked pathways [ 62 , 63 ]. In vivo PET studies also show stronger and more frequent association between microglial activation (measured with TSPO PET) and regional tau (measured with tau PET), than with regional Aβ (measured with amyloid PET) [ 64 ]. Here, they also found a positive correlation between CSF sTREM2 and tau PET in 4-repeat tau patients, but no correlation between CSF sTREM2 and amyloid PET [ 64 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings are in line with in vivo observations that point to associations between microglial activation and tau pathology, and with recent large GWAS studies underscoring the interaction between microglial, Aβ and tau-linked pathways [ 62 , 63 ]. In vivo PET studies also show stronger and more frequent association between microglial activation (measured with TSPO PET) and regional tau (measured with tau PET), than with regional Aβ (measured with amyloid PET) [ 64 ]. Here, they also found a positive correlation between CSF sTREM2 and tau PET in 4-repeat tau patients, but no correlation between CSF sTREM2 and amyloid PET [ 64 ].…”
Section: Discussionmentioning
confidence: 99%
“…In vivo PET studies also show stronger and more frequent association between microglial activation (measured with TSPO PET) and regional tau (measured with tau PET), than with regional Aβ (measured with amyloid PET) [ 64 ]. Here, they also found a positive correlation between CSF sTREM2 and tau PET in 4-repeat tau patients, but no correlation between CSF sTREM2 and amyloid PET [ 64 ]. Moreover, others have also reported elevated concentrations of CSF glial activation markers in SNAP cases (A−/T+) [ 65 67 ].…”
Section: Discussionmentioning
confidence: 99%
“…125 Indeed, neuroinflammation and microglial activation are consistent features across neurodegenerative diseases, including AD, [126][127][128] PD, 86,129 HD, 130,131 FTD, 91,132 and ALS. 89,[133][134][135] Numerous studies have reported that misfolded proteins and protein aggregates, including tau, [136][137][138][139] Aβ, 138,140 α-synuclein, [141][142][143][144] mutant huntingtin, 145 TDP-43, 132,146 superoxide dismutase 1 (SOD1), [147][148][149] and fused in sarcoma (FUS) 150 induce microglial activation and neuroinflammation. Autophagy deficiency induced by protein aggregates has been shown to be a major driver of microglial activation (Fig.…”
Section: Roles Of Microglia In Neurodegenerative Diseasesmentioning
confidence: 99%
“…It can also be used to assess the viability of brain tissue in regions at risk of infarction before interventional procedures such as carotid endarterectomy. It can also be utilized for the detection and characterization of cerebral amyloid deposition in disorders like Alzheimer’s disease ( 89 , 90 ). The use of specific amyloid-targeting tracers allows for the quantification of amyloid plaques in the brain, aiding in diagnosis and monitoring disease progression ( 91 , 92 ).…”
Section: Petmentioning
confidence: 99%